Survival of the Recidivistic? Revealing Factors Associated with the Criminal Career Length of Multiple Homicide Offenders - Campedelli, Gian Maria (Homicide studies, 2022)
Relying on a sample of 1,381 US-based multiple homicide offenders (MHOs), we study the duration of the careers of this extremely violent category of offenders through Kaplan–Meier estimation and Cox Proportional Hazard regression. We investigate the characteristics of such careers in terms of length and we provide an inferential analysis investigating correlates of career duration. The models indicate that MHOs employing multiple methods, younger MHOs and MHOs that acted in more than one US state have higher odds of longer careers. When controlling for career-based attributes, female MHOs are also correlated with longer careers.